CLIL AND GLOBAL EDUCATION: A MEANINGFUL MATCH - Strakova, Zuzana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Education for future necessarily embraces multiple skills and themes which are transversal and applicable across the curriculum content. Students need to see and understand the content of individual subjects as connected and not as a discrete entity. CLIL as an approach which focuses on integration of meaningful context into a language learning classroom has been tested over the last decades and demonstrates that communication does not necessarily need to be limited to vocabulary and grammar practice. On the contrary as one of the global skills communication supports social interaction in problem solving, collaboration and thus is the key skill in achieving target goals. This study focuses on the readiness to implement the global skills within the CLIL approach among trainees in their last year of teacher training in Slovakia in 2019. The questionnaires and the subsequent interviews reveal that future language teachers still seem to prefer focusing on pure language aims to integrating global skills development and they even lack the confidence in application of transversal themes and skills. Even though there is a clear understanding of the importance of integration of global skills into education in general the lack of their own experience seems to determine their attitude towards them. These results identify the space for modification in the teacher training curriculum; however, it requires a wider cooperation within different subjects.